2023
DOI: 10.1371/journal.pone.0277478
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, and characterisation of the p53 binding domain of Retinoblastoma binding protein 6 (RBBP6)

Abstract: RBBP6 is a 250 kDa eukaryotic protein known to be a negative regulator of p53 and essential for embryonic development. Furthermore, RBBP6 is a critical element in carcinogenesis and has been identified as a potential biomarker for certain cancers. RBBP6’s ability to interact with p53 and cause its degradation makes it a potential drug target in cancer therapy. Therefore, a better understating of the p53 binding domain of RBBP6 is needed. This study presents a three-part purification protocol for the polyhistid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…Accumulating studies have demonstrated that p53 is mutated in various cancers; however, most individuals with CC express wtp53 [25,26]. Recent studies have reported that p53 is negatively regulated by the retinoblastoma binding protein 6 (RBBP6) gene, a eukaryotic protein with a size of 250 kDa, responsible for embryonic development [27]. The RBBP6 gene is alternatively spliced to generate three protein isoforms that are differentially expressed in different tumor stages, with more advanced cancers exhibiting higher levels of RBBP6 compared to less advanced stages [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have demonstrated that p53 is mutated in various cancers; however, most individuals with CC express wtp53 [25,26]. Recent studies have reported that p53 is negatively regulated by the retinoblastoma binding protein 6 (RBBP6) gene, a eukaryotic protein with a size of 250 kDa, responsible for embryonic development [27]. The RBBP6 gene is alternatively spliced to generate three protein isoforms that are differentially expressed in different tumor stages, with more advanced cancers exhibiting higher levels of RBBP6 compared to less advanced stages [28,29].…”
Section: Introductionmentioning
confidence: 99%